1984
DOI: 10.1111/j.1398-9995.1984.tb00873.x
|View full text |Cite
|
Sign up to set email alerts
|

Hyposensitization with a Tyrosine Adsorbed Extract of Dermatophagoides pteronyssinus in Adults with Perennial Rhinitis

Abstract: Hyposensitization with a tyrosine adsorbed extract of Dermatophagoides pteronyssinus was effective in relieving symptoms in selected patients with perennial rhinitis due to this allergen who had responded poorly to topical application of steroids. There was a significant reduction in the nasal response to allergen after six weekly injections only in the actively treated group, but symptomatic improvement greater than that produced by placebo therapy was only evident after a further 10 months of monthly injecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0
2

Year Published

1990
1990
2007
2007

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 11 publications
(4 reference statements)
2
20
0
2
Order By: Relevance
“…By way of contrast, prevalence of skin test positivity is < 10% in asymptomatic populations [34,35]. Nasal insuffiation with house-dust mite extract reproduces the symptoms of rhinitis in sensitized people, and there are several trials that have indicated benefit of immunotherapy with mite extracts in the treatment of this condition [36][37][38][39]. Thus, there is substantial evidence to link house-dust mite hypersensitivity with the expression of rhinitis.…”
Section: Rhinitismentioning
confidence: 99%
“…By way of contrast, prevalence of skin test positivity is < 10% in asymptomatic populations [34,35]. Nasal insuffiation with house-dust mite extract reproduces the symptoms of rhinitis in sensitized people, and there are several trials that have indicated benefit of immunotherapy with mite extracts in the treatment of this condition [36][37][38][39]. Thus, there is substantial evidence to link house-dust mite hypersensitivity with the expression of rhinitis.…”
Section: Rhinitismentioning
confidence: 99%
“…Nine studies investigated other pollen allergens: mountain cedar (10,27,29), Parietaria (42,43,46), Cupressus (45), Cocos (41), and mixtures (6); efficacy was demonstrated in six. The efficacy of house-dust-mite immunotherapy (14,24,26,28,33) was based on five studies (three showing efficacy). In mold allergies, efficacy was documented in one study investigating Alternaria (31).…”
Section: Clinical Efficacy Of Immunotherapy In Rhinitismentioning
confidence: 99%
“…Two recent papers have reported a positive effect on nasal symptoms (9,14), whereas in two L. HAUGAARD ET AL. other studies a positive effect has been shown, but only in some of the parameters examined (4,15).…”
Section: B Rhinitismentioning
confidence: 71%